Small sacrifices : religious change and cultural identity among the Ngaju of Indonesia - Schiller, Anne (Anne Louise) (OUP E-Books., 1997)
This ethnographic study shows how the Ngaju Dyaks, rain forest dwellers of Central Kalimantan (Indonesian Borneo) are responding to modernity. It depicts how they are attempting to fashion a modern identity for themselves, especially by remodelling their indigenous religion.